Age, Sex, Education, Emotional Intelligence, Cognitive Intelligence, and Management Level: A Study from Great Britain. (April 2023) - Treglown, Luke; Furnham, Adrian
Do non-, first-line, middle and senior managers differ in their cognitive ability and emotional intelligence? In this study we interested in the demographic and ability differences of people at different management levels. Over 6000 adults completed a multidimensional intelligence test (IQ) with five subscales and a measure of Trait Emotional Intelligence (EQ) with 15 subscales. First, we examined sex, age, educational and management level correlates of both EQ and IQ. Whilst there were many significant results, effect sizes were small. The focus of the paper was the regression using management level as the criterion variable and demography, EQ and, IQ as the predictor variables at facet and domain levels. Age and sex, particularly the former, accounted for nearly 30% of the variance, but both EQ and IQ added incremental variance. Facet level variance showed that specifically IQ number speed, and EQ sociability and emotionality (negatively) related to managerial level. Implications for general management and limitations are acknowledged.